Incorporation of terminal phosphorothioates into oligonucleotides. - Alefelder, S (1998)
Considerable effort has been directed towards studying the structure and function of oligonucleotides and several approaches rely on the attachment of reporter groups to oligonucleotides. We report here the introduction of 3'- and 5'-terminal phosphorothioates into heptameric oligonucleotides and their post-synthetic modification with several reporter groups. The synthesis of terminal phosphorothioates is based on the coupling of a ribonucleoside phosphoramidite at the first or last nucleotide, respectively, which, after sulphurization, is removed by sequential oxidation of the vicinal hydroxyl groups and then beta-elimination. Product formation is of the order of 95%. The ratio of phosphorothioate- versus phosphate-terminated oligodeoxynucleotides as analysed by electrophoresis on a Hg2+gel is in general 85/15. Examples for the reactivity of the terminal phosphorothioates for conjugation with cholesterol, bimane and for sulphydryl exchange are described.